PENGENALAN BUDAYA ISLAM BANJAR MELALUI SASIRANGAN SEBAGAI MEDIA UNTUK PEMBELAJAR BIPA MUSLIM-MELAYU THAILAND - Auliana, Nisa (UIN ANTASARI BANJARMASIN, 2024)
Indonesian has an important role to be learned by the Thai community, especially the Thai Malay community. This is evidenced by the use of Indonesian in education in several regions in Thailand. BIPA (Indonesian for Foreign Speakers) learning is closely related to the introduction of culture. In addition to the familiarization method, this research also integrates Sasirangan fabric making process training into BIPA learning. This research uses an exploratory approach and is qualitative in nature, focusing on the learning implementation process. The research subjects consisted of 70 students participating in the BIPA program and Sasirangan training at Ma'had Al-Irsyad Lil-Banat, Yala, South Thailand. Data were collected through observation, hands-on training, recording of activity results, and question and answer sessions, and analyzed descriptively. The results showed that the Menyirang training significantly improved participants' Indonesian vocabulary, based on post-training evaluations. The process also encouraged cultural appreciation, with learners actively discussing Banjar culture and Sasirangan patterns. The interactive nature of the training increases the efficiency of language acquisition, as participants frequently ask questions and practice vocabulary in context. The integration of Sasirangan into BIPA learning not only enriches language comprehension, but also effectively introduces Banjar cultural heritage. These results confirm the importance of combining language learning with cultural recognition to achieve holistic educational outcomes.